Kepemimpinan Transformasional sebagai Katalisator Inovasi dan Kinerja Organisasi: Tinjauan Literatur - Asbari, Masduki; Novitasari, Dewiana (AGUSPATI RESEARCH INSTITUTA, 2024)
Transformational leadership has been widely recognized as an effective leadership style in driving innovation, improving performance, and shaping adaptive organizational culture. This article aims to comprehensively examine the influence of transformational leadership on innovation, performance, and organizational culture through a literature review. This research identifies four key dimensions of transformational leadership-idealized influence (charisma), inspirational motivation, intellectual stimulation, and individualized consideration-that contribute to the achievement of organizational goals and individual development. The results of the literature review indicate that transformational leaders are not only able to improve performance and drive innovation, but also build an organizational culture that supports collaboration, openness to change, and empowerment of team members. The practical implications of this study emphasize the importance of developing transformational leadership skills to create an environment that motivates employees, encourages creativity, and ensures the sustainability of innovation in organizations. In addition, this study also provides insight into the role of readiness to change in enhancing transformational leadership effectiveness. Theoretically, this article enriches the literature on transformational leadership, providing new perspectives on the application of this leadership style in the context of dynamic organizational change.